Analisis Cost Volume Profit Sebagai Dasar Perencanaan Laba Yang Diharapkan - Yunda Kusumaningayu; Rusman Soleman; Rizky Wahyu Utami Ohorella (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Cost Volume Profit Analysis as a Basis for Expected Profit Planning (Case Study of Privately Owned Business "Ifamoy Home Industri"). Under the guidance of A company needs profit planning to help management determine the level of profit it wants to obtain, with Cost Volume Profit analysis which focuses on various factors that influence changes in profit components at the Ifamoy Home Industry company. This research aims to determine the application of Cost Volume Profit Analysis in the Ifamoy Home Industry. This research uses descriptive research. The data collection technique used is the Observation and Documentation Technique on existing income data at Ifamoy Home Industry. The results of this research show that the Total Calculation Profit is IDR. 828,000,0000.00, with a total Contribution Margin of IDR. 1,670,000,000 with a ratio of 0.8%, with a Total Break Even Point of Rp. 512,000,000, with a total margin of safety of Rp. 1,568,000,000, with a ratio of 75%, with profit planning to increase by (20%) in 2023 resulting in a profit of Rp. 2,508,200,000.